Сraudfanding as a model of investment (legal aspect) - Бударна, Віталія Олексіївна (Problems of legality, 2018)
In the article analyzed crowdfunding as an innovative investment model. Singled out the sub-categories of the crowdfunding that can exist in the system of these relations. And as a conclusion, noted that such a model of investment relations as crowdfunding is quite promising today in Ukraine. The socio-economic phenomenon of a special type of relations, known as crowdfunding, was researched. Certain types of crowdfunding have been identified and singled out, among which a number of features of investment-type relations are characteristic. It was concluded that the crowdfunding does not contradict the current model of investment policy of the state and the content of investment legislation of Ukraine. On this basis, it is argued that craftfunding requires a direct legal regulation in the current investment legislation of Ukraine. Attention was drawn to the need to delineate the crowdfunding, which has a philanthropic orientation from the investment landscape of the Crowdfunding. The article points out the expediency of borrowing the Scandinavian model of crowdfunding and the need for the introduction of local and regional investment projects that would provide the most crowding-up mechanism for their investment. Legislative differentiation of funds attraction on the kraudfanding basis as a mechanism of charity and as a mechanism of investment. (It is also important to further distribute investment custodian to commercial and one that is carried out for a social effect.) Stimulate the creation of local and regional investment projects, as potential investors of the Crowdfunding model are much more willing to provide funds for the development of their own city or oblast than on national projects. Creation of a professional intermediary institution, which would be designed to ensure the balance of interests between the parties, carried out an analysis of the market and the project itself, and the prospects for its implementation. Realize crudfangdom relations with the help of the current model of technology parks, since they are supported by the state, controlled by it, have legislative guarantees and tax privileges and a higher probability of achieving a positive result.